Anaerobic Capacity Level Differences of Each Player Position in Volleyball - Muhamad Wilman Nugraha; L Lily (Universitas Pendidikan Indonesia, 2022)
Volleyball is one of the most popular sports in the world. To be a professional volleyball player, a coach needs to know how to train their athletes. According to the physiological component, the most used energy of a volleyball player comes from ATP-PC and glycolysis. This study aimed to classify an anaerobic capacity standard of male volleyball athletes in Indonesia. In this study, 60 athletes participated in 2 levels: Junior 15-17-year-old High School student level and 18-25-year-old University student level. The samples were chosen according to their achievement in national-level competitions in the last few years. The measurement used the Running Anaerobic Sprint Test, Vertical Jump Test, and 5-Meter Multiple Shuttle Repeat Sprint Test. The analysis employed an ANOVA test using SPSS 16 and Tukey post hoc test. This study found differences in several anaerobic performance aspects of each position in the same level of competition and at the different levels of competition. In the junior-level athletes, a significant difference was found in the average power between outside hitter and libero, peak power vertical jump between middle blocker and libero, and total distance achieved among outside hitter, opposite hitter, and setter. Senior-level athletes showed a significance different in maximum power, average power, and fatigue index of outside hitters, middle blocker, opposite hitters, setter, and libero, peak power of vertical jump among hitters, setter, and libero, and total distance achieved by hitters, setter, and libero. In conclusion, senior-level athletes showed superiority shown by higher scores of anaerobic capacity than junior-level athletes. It is suggested to conduct more research on the characteristics of each position in volleyball to train athletes more effectively and efficiently according to their position.